Serum CA72-4 is specifically elevated in gout patients and predicts flares - Bai, Xueshan (Rheumatology (Oxford), 2020)
OBJECTIVES: Serum CA72-4 levels are elevated in some gout patients but this has not been comprehensively described. The present study profiled serum CA72-4 expression in gout patients and verified the hypothesis that CA72-4 is a predictor of future flares in a prospective gout cohort. METHODS: To profile CA72-4 expression, a cross-sectional study was conducted in subjects with gouty arthritis, asymptomatic hyperuricaemia, four major arthritis types (OA, RA, SpA, septic arthritis) and healthy controls. A prospective gout cohort study was initiated to test the value of CA72-4 for predicting gout flares. During a 6-month follow-up, gout flares, CA72-4 levels and other gout-related clinical variables were observed at 1, 3 and 6 months. RESULTS: CA72-4 was highly expressed in patients with gouty arthritis [median (interquartile range) 4.55 (1.56, 32.64) U/ml] compared with hyperuricaemia patients [1.47 (0.87, 3.29) U/ml], healthy subjects [1.59 (0.99, 3.39) U/ml] and other arthritis patients [septic arthritis, 1.38 (0.99, 2.66) U/ml; RA, 1.58 (0.95, 3.37) U/ml; SpA, 1.56 (0.98, 2.85) U/ml; OA, 1.54 (0.94, 3.34) U/ml; P < 0.001, respectively]. Gout patients with frequent flares (twice or more in the last year) had higher CA72-4 levels than patients with fewer flares (fewer than twice in the last year). High CA72-4 level (>6.9 U/ml) was the strongest predictor of gout flares (hazard ratio = 3.889). Prophylactic colchicine was effective, especially for patients with high CA72-4 levels (P = 0.014). CONCLUSION: CA72-4 levels were upregulated in gout patients who experienced frequent flares and CA72-4 was a useful biomarker to predict future flares.